Transport of diamines by Enterococcus faecalis is mediated by an agmatine-putrescine antiporter. - Driessen, A J (1988)
Enterococcus faecalis ATCC 11700 is able to use arginine and the diamine agmatine as a sole energy source. Via the highly homologous deiminase pathways, arginine and agmatine are converted into CO2, NH3, and the end products ornithine and putrescine, respectively. In the arginine deiminase pathway, uptake of arginine and excretion of ornithine are mediated by an arginine-ornithine antiport system. The translocation of agmatine was studied in whole cells grown in the presence of arginine, agmatine, or glucose. Rapid uncoupler-insensitive uptake of agmatine was observed only in agmatine-grown cells. A high intracellular putrescine pool was maintained by these cells, and this pool was rapidly released by external putrescine or agmatine but not by arginine or ornithine. Kinetic analysis revealed competitive inhibition for uptake between putrescine and agmatine. Agmatine uptake by membrane vesicles was observed only when the membrane vesicles were preloaded with putrescine. Uptake of agmatine was driven by the outwardly directed putrescine concentration gradient, which is continuously sustained by the metabolic process. Uptake of agmatine and extrusion of putrescine by agmatine-grown cells of E. faecalis appeared to be catalyzed by an agmatine-putrescine antiporter. This transport system functionally resembled the previously described arginine-ornithine antiport, which was exclusively induced when the cells were grown in the presence of arginine.